Stem Cell a Solution May Help to Treatment for Pandemic COVID-19 - F. G. Mistrih; N. G. Mistrih; G. Eghon (Research Aspects in Biological Science Vol. 2, 2022)
In China, an infection of the virus was generated, which has not been effectively treated, that is why we justify expanding our knowledge of a therapeutic option that appears, beyond being a preventive treatment, the effectiveness of IV mesenchymal cell transplantation, has not been presented with final conclusion which permit scientists to recommend it as the only treatment, but Investigation in various pathologies revealed a very favorable immune reaction, modulating inflammatory cascades in inflamed problems. Furthermore, it clearly illustrates a regeneration of it (which is the same) that has powerfully captured the attention of doctors when treating autoimmune, degenerative, and chronic pathologies, which to date have no palliative therapies, such as SLE, post-infarction heart disease, chronic arthritis, Alzheimer’s, and among others, many laboratory tests were essential, due to urgent need of frustrated patients due to the few therapeutic options which led to the use of mesenchymal cells for their treatment. Because the pneumonias induced by this new virus are rapidly progressing and fatal, with little effective treatment, we have advocated regulating cytosines through the transplantation of mesenchymal cells, as these are the main sources of problems due to their increased systemic reactivity. We studied in different pathologies the use of stem cell to improve the quality of life of patients.